Prosthodontic considerations in geriatric patients addressing age-related oral changes - Salem Alfaer, Ali; IbnLadnah, Saad Saeed; Alshehri, Abdulrahman Ali; Almujahid, Muath Mohammed; Shami, Mohammed Taleb Bin (International Journal Of Community Medicine And Public Health, 2025)
Aging leads to significant physiological changes in the oral cavity, presenting unique challenges in the management of oral health in elderly patients. Common conditions such as xerostomia, periodontal disease, and denture-related complications are prevalent and often compounded by systemic health issues, medication side effects, and socioeconomic barriers. Effective management requires a comprehensive approach that integrates clinical interventions, preventive strategies, and patient-specific care plans. Xerostomia, frequently caused by polypharmacy, affects oral lubrication and increases the risk of dental caries. Management strategies include the use of saliva substitutes, stimulants like xylitol-based lozenges, and enhanced hydration practices. Periodontal disease, often exacerbated by systemic conditions like diabetes, demands regular mechanical debridement, antimicrobial therapy, and patient education on oral hygiene. Tailored solutions, such as modified toothbrushes and flossing tools, accommodate reduced dexterity in elderly patients. Denture-related conditions such as stomatitis and pressure sores are addressed through proper denture fitting, use of tissue conditioners, and antifungal treatments. Emphasis on improved prosthesis hygiene reduces microbial colonization and enhances comfort. Nutritional deficiencies linked to oral conditions are managed through dietary modifications, counseling, and nutrient supplementation, ensuring adequate intake of essential vitamins and minerals. Socioeconomic barriers and mobility challenges often hinder access to regular dental care in the elderly. Mobile dental units, community outreach programs, and public health initiatives have been effective in bridging these gaps. Psychosocial support, including empathetic communication and caregiver involvement, plays a vital role in ensuring adherence to treatment plans. Holistic management of oral health in elderly patients enhances not only oral function but also overall well-being, demonstrating the importance of integrating medical, nutritional, and social considerations in geriatric dentistry. This multifaceted approach improves quality of life and addresses the complex needs of aging populations.